The future of American intelligence - Berkowitz, Peter ([Hoover Institution Press publication)
Introduction / Peter Berkowitz -- The era of armed groups / Richard Shultz -- Truth to power : rethinking intelligence analysis / Gary Schmitt -- Restructuring the intelligence community / Gordon Lederman -- A new clandestine service : the case for creative destruction / Reuel Mark Gerecht -- The role of science and technology in transforming American intelligence / Kevin O'Connell.